The Evolving Landscape Of Breast Cancer Treatment: From Conventional Approaches To Emerging Innovations - Kamal, Preeti; Ansari, Zeeshan; Neha, Neha; Chaurasia, Ayush; Sinha, Asmit; Tiwari, Mamta (Journal of Neonatal Surgery, 2025)
Breast cancer remains one of the most prevalent malignancies worldwide, necessitating continuous advancements in treatment strategies to improve patient outcomes. This review explores the current landscape of breast cancer therapies, ranging from conventional approaches such as surgery, radiation therapy, and chemotherapy to emerging targeted and immunotherapeutic modalities. The primary objective of this review is to provide a comprehensive analysis of modern breast cancer treatments, highlighting their mechanisms of action, clinical efficacy, resistance mechanisms, and future directions. Recent advances in targeted therapy, particularly HER2 inhibitors, tyrosine kinase inhibitors (TKIs), CDK4/6 inhibitors, PI3K/AKT/mTOR pathway inhibitors, and PARP inhibitors, have revolutionized breast cancer management, significantly enhancing survival rates. Immunotherapy, including immune checkpoint inhibitors, has shown promise, particularly for triple-negative breast cancer. Despite these advancements, treatment resistance and adverse effects remain significant challenges, necessitating ongoing research into combination strategies, biomarker-driven therapies, and novel therapeutic targets. To ensure a robust and up-to-date synthesis, a structured search strategy was employed across PubMed, Scopus, and Web of Science databases. The search focused on peer-reviewed articles, clinical trials, and meta-analyses published in the last 10 years using keywords such as breast cancer, targeted therapy, immunotherapy, drug resistance, HER2 inhibitors, and precision medicine. Studies were selected based on relevance, clinical significance, and methodological rigor. Future research will focus on overcoming therapeutic resistance, refining combination regimens, and integrating biomarker-driven precision medicine to optimize patient-specific treatment approaches. A multidisciplinary approach, incorporating genomic profiling, immunotherapy, and next-generation targeted therapies, holds the potential to transform breast cancer care and improve long-term survival and quality of life